Sensitivity limitation of a SQUID gravity gradiometer due to elastic interaction between sensing currents and test masses. - Zarembinski, S. (IEEE Transactions on applied superconductivity)
Differential displacement due to a gravitational force gradient, acting on two superconducting test masses which are elastically suspended from the instrument frame, is sensed by a superconducting quantum interference device (SQUID) coupled to the masses by a current flowing in the sensing circuits. An elastic interaction between the sensing currents and the currents mirrored on the superconducting surfaces of the test masses can stiffen the movement of the masses, reducing the sensitivity of the instrument. However, this interaction is not principally limiting, and the SQUID can be built so that stiffening does not occur